Development of the Muslim Religiosity-Personality Inventory for Measuring the Religiosity of Malaysian Muslim Youth - Krauss, Steven Eric (2005)
Religiosity from the Islamic perspective has not been thoroughly represented or investigated. The lack of an appropriate conceptualization and measurement instrument reflective of the unique Islamic tawhidic worldview has hindered efforts to capture key elements of religious understanding and practice among young Muslims in Malaysia. In response to this need, this study set out to 1) develop a comprehensive model of religiosity from the Islamic perspective; 2) develop an appropriate measurement instrument based on the religiosity model; and 3) use the religiosity instrument to establish religiosity norms (normed scores) and benchmarks for key demographic sub-groups of Malaysian Muslim youth. To achieve the objectives, the study incorporated a basic exploratory-descriptive research design. To address the above problem and objectives, the author conducted a major review of the Islamic and non-Islamic literatures on religiosity to develop the Islamic religiosity model. From the religiosity model and its operational definitions, the religiosity instrument - the Muslim Religiosity-Personality Inventory (MRPI) - was developed and pilot tested to ensure reliability and validity. The MRPI was then field tested among 1,692 youth fiom across Malaysia. From the field test data, raw scores were obtained and normed using a standardized (z-score) method. The normed scores were then compared across five demographic variables (i.e. cluster group, age group, sex, level of educational attainment and place of residence) using descriptives, T-test and ANOVA. The normed scores were then compiled to establish religiosity benchmarks for Malaysian Muslim youth as a relative standard of comparison for future MRPI respondents. The study findings indicated that a model and instrument for measuring religiosity fiom the Islamic perspective is attainable. The MRPI is based on a multi-dimensional and comprehensive religiosity concept reflective of key dimensions of the Islamic tawhidic worldview. The field test findings indicated that there are significant differences in youth religiosity normed scores across the six sub-populations of youth sampled (i.e. IPTA students, youth organization members, Serenti drug rehabilitation inmates, political party members, youth 'at-large' and young factory workers), as well as across most of the other five demographic variables. Overall, the study concluded that there are considerable differences in religiosity among different groupings of Muslim youth in Malaysia, which potentially reflects differences in key competencies integral for positively contributing to nation building. The study also points to several important areas for future religiosity research among youth in Malaysia using the MRPI and resulting religiosity benchmarks.